Constructing the audio format in the performance of the theater actor: يــاسين إسماعيل خلـف - فائـــــز طـــــــــــــه ســــــــالم (Al-Academy, 2020)
The science of (- - Semiology) comes in the introduction to language sciences and linguistics that addressed the levels of language building and its phonemic signs, through which we can monitor and analyze the data of the phoneme of the actor, and the ways to build his linguistic speech, especially since (the linguist Saussure - He emphasized that linguistque is only part of the science of signs, which is particularly advanced within logic, social psychology, and general psychology, and since language is in the origin - whatever language, and at what level - it is not A separate, single and unified language, in fact, they are intertwined, multiple, varied and renewed languages due to their influence The times and its development and the interplay of their vocal expressions, especially with the technical development of the means of communication and the digital revolution. The studies (semi-semiology) that deal with language with aesthetic description (creative) , but are based on the study of (their performance competencies) , as well as their linguistic competencies, by monitoring The network of phoneme performance, in order to achieve a true manifestation of (the language of dispatched discourse) , far from confining it to the utilitarian function and material truth, in favor of the semantic function and its aesthetic symbolic role, so it becomes natural for the phoneme format in the speech of the theatrical actor to form a greater and broader semantic momentum from his linguistic reference Inside the text durr My mother, the (Dramatic Reference) can be matched by a linguistic linguistic sign, or a semi-linguistic phonetic expression, and this allows the semantic (non-linguistic) phoneme sign to create the semiotic vocabulary constructed by the literal functions themselves, and where our research is determined by the formats of building the phonemic performance of the actor as a complex aesthetic, scientific d. Knowing and revealing the nature of compromise in it and the levels of building its relationships with (the meaning) becomes a goal that the research seeks to achieve as it constitutes a knowledge and artistic aspect in the creative personification process of the actor, and this categorical classification does not contradict with the idea that the process of embodiment is formed from the convergence and harmony of a group of sound formats And other dynamics) In turn, within a network of relationships, they refer to the functions of the presentation elements in each unit.We summarize the most important results and conclusions of our research with the following points: The acoustic mark in the speech of the actor (linguistic) in the process of permanent installation, organized according to the diversity of its relations with the reference.The phoneme is an aesthetic arrangement, the fruit of adopting relationships based on a synchronous basis, an approach that monitors the deep structures of the linguistic sign, by transcending the limits of concern for the apparent meaning of the word and the sentence, in favor of the hidden meaning in the overall discourse of presentation.The phoneme format begins as an icon and then transforms into a sign by transcending the traditional relationships of the spoken word or phonemic expression and their sequential structures, with the aim of allowing relationships already existing to appear in a new context in which they were not previously realized.The linguistic speech of the actor is completed, and he acquires his aesthetic specificity, in that it is a scientific coded format with phonetic expressions, based on its structure based on the compatibility of grammatical formats (linguistic competencies of language) - grammatical - morphological - lexical - phonetic - and expressive formats (semi-linguistic performance competencies) - techniques, Expressive audio skills.